2020
DOI: 10.1016/j.compag.2020.105394
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of low-cost depth cameras for agricultural applications

Abstract: Low-cost depth-cameras have been used in many agricultural applications with reported advantages of low cost, reliability and speed of measurement. However, some problems were also reported and seem to be technologyrelated, so understanding the limitations of each type of depth camera technology could provide a basis for technology selection and the development of research involving its use. The cameras use one or a combination of two of the three available technologies: structured light, time-of-flight (ToF),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…In this study, the distance between the camera and the floor was 2.25 m, which made it possible to capture the entire pen. Previous studies have reported shorter distances than that utilized in the present study, for example, 1.7 m above the ground ( Condotta et al, 2020 ) or 1.0–1.2 m above the pig ( Pezzuolo et al, 2018a ). A longer camera clamp may be required to reduce the distance to be either equal to or less than 2 m in future experiments to obtain more accurate depth data.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In this study, the distance between the camera and the floor was 2.25 m, which made it possible to capture the entire pen. Previous studies have reported shorter distances than that utilized in the present study, for example, 1.7 m above the ground ( Condotta et al, 2020 ) or 1.0–1.2 m above the pig ( Pezzuolo et al, 2018a ). A longer camera clamp may be required to reduce the distance to be either equal to or less than 2 m in future experiments to obtain more accurate depth data.…”
Section: Discussionmentioning
confidence: 53%
“…The second factor was the distance between the sensor and the pig. It has been reported that random error measurements increase with increasing distance between the sensor and the object ( Condotta et al, 2020 ). In this study, the distance between the camera and the floor was 2.25 m, which made it possible to capture the entire pen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-cost consumer 3D depth-sensor cameras, such as Microsoft Kinect (Microsoft, Redmond, WA) and Intel RealSense (Intel, Santa Clara, CA), have been used to predict morphological characters and monitor animal behavior ( Condotta et al, 2020 ). A depth-sensor camera positioned at the ceiling visualizes animals in a 3D space by adding height information using the time-of-flight or structured light technology.…”
Section: Computer Visionmentioning
confidence: 99%
“…Desspite superior performance on Visual Odometry (VO), other works present the relevant errors in many applications when comparing point clouds’ accuracy generated from structured light and stereo sensors. In [ 41 ], several cameras are analyzed and compared in length and area accuracy in terms of pixel coefficients. Even though the ZED camera presents good and sometimes the best results in outdoor applications, there are more flaws and inaccuracies in close objects, with depth deviations that lead to wrong measurements of volume and area.…”
Section: 3d Reconstruction Heterogeneous Edge Environments and Rmentioning
confidence: 99%